Epidemiology and Seasonal Variation of Ixodid Ticks and Piroplasmida Detection in Cattle of Basrah Province, Iraq (Indian Journal of Forensic Medicine & Toxicology, 2020)
Four hundred and twenty cattle belonging to different breed and age groups were investigated for infestationby ticks during the period from October 2018 to September 2019 in Basrah governorate, Iraq . Investigatedcattle were found to be infested by four species of hard ticks namely (Hyalomma anatolicum anatolicum, Hyalomma marginatum turanicum Rhipicephalus (Boophilus) annulatus, Rhipicephalu sturanicus) .Nosignificant difference in infestation rate was observed according to the method of cattle raising (X²=0.455,p=0.500),however, seasonal variation in infestation with significant difference was found , higher infestationrate reported in June ( 63.3%) and the lowest was in January (20%) (X² =76.740 ,p = 0.05). In the meantimeblood smears samples from the same cattle were also examined by microscopy for hemoprotozoan pathogens.The examination revealed that those cattle are infected by Babesia spp. (27.14%) and Theileria spp.(19.52%).No, significant difference in infection rate was found between male and females, but a significant variationwas seen among age groups, however, age group 1-3 years revealed a high rate of infection .Seasonalvariation in the infection rates were observed in infected cattle. Higher infection rates of Babesiosis andTheileriosis reported in June (50%) and (36.7%) respectively.
Keywords: Epidemiology, Babesia bovis, Theileria annulata , Hyalomma, Rhipicephalus, Basrah, Iraq.